PENGGUNAAN MEDIA PEMBELAJARAN VIDEO INTERAKTIF PADA MUATAN PEMBELAJARAN IPA UNTUK SISWA SEKOLAH DASAR - Eha Pitriyanita; Widiyatmoko, Arif; Handayani, Langlang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Natural Sciences (IPA) is one of the disciplines of science that is very important in everyday life to help improve the learning outcomes of elementary school students and help students in understanding the material for problem solving. This study aims to see the feasibility of using interactive video learning media in the science learning content for elementary school students. The research method used in this study is a qualitative research method with literature study techniques from various previous studies using Google Scholar and Scopus which are then collected and analyzed to show the effectiveness of using interactive video learning media in the science learning process. The results of this study are that interactive video media has been proven to be able to be used to help in the learning process in science content for elementary school students.